The solution is [tex]x=4[/tex]
Step-by-step explanation:
The starting equation is
[tex]1-2x=-x-3[/tex]
The first step to do is to bring all the terms in the variable on the same side. To do that, let's start by adding [tex]+2x[/tex] on both sides:
[tex]1-2x+2x = -x-3+2x[/tex]
and we get
[tex]1=-3+x[/tex]
Now we add +3 on both sides:
[tex]1+3=-3+x+3[/tex]
And we get
[tex]4=x[/tex]
So the solution is [tex]x=4[/tex].
Learn more about equations:
brainly.com/question/13168205
brainly.com/question/3739260
#LearnwithBrainly